Bioinspired hybrid eumelanin–TiO2 antimicrobial nanostructures: the key role of organo–inorganic frameworks in tuning eumelanin's biocide action mechanism through membrane interaction. Issue 50 (7th August 2018) - Vitiello, Giuseppe; Zanfardino, Anna; Tammaro, Olimpia; Di Napoli, Michela; Caso, Maria Federica; Pezzella, Alessandro; Varcamonti, Mario; Silvestri, Brigida; D'Errico, Gerardino; Costantini, Aniello; Luciani, Giuseppina
Abstract : Hybrid TiO2 /eumelanin nanostructures showed a peculiar biocide mechanism against Gram(−) bacteria, based on the ROS action, produced by eumelanin degradation under visible light irradiation, and the interactions with external bacterial membranes. Abstract : Intrinsic biocide efficacy of eumelanins can be markedly enhanced through a templated formation in the presence of a TiO2 -sol, leading to hybrid TiO2 –melanin nanostructures. However, mechanisms and processes behind biocide activity still remain poorly understood. This paper discloses the fundamental mechanism of action of these systems providing mechanistic information on their peculiar interaction with Escherichia coli strains. To this purpose biocide characterization is combined with Electron Paramagnetic Resonance (EPR) spectroscopy to investigate radical species produced by the hybrids as well as their interactions with Gram(−) external bacterial membranes. Experimental results indicate that TiO2 mediated eumelanin polymerization leads to a peculiar mechanism of action of hybrid nanostructures, whose strong interactions with bacterial membranes enhance the action of reactive oxygen species (ROS) produced by eumelanin degradation itself, also concurring with the final biocide action. These findings provide strategic information for the development of eumelanin-based systems with enhanced activity against drug-resistant strains.